Capacity Analysis of Downstream Cijangkelok River Using HEC-RAS Software - Anggista, Dhea; Zahra, Farach Alifia; Mariani, Nadia; Winasis, Akbar (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the capacity of the Cijangkelok River downstream in facing the planned flood discharge, with a hydraulic modeling approach using HEC-RAS software. Maximum daily rainfall data from five rainfall stations during the 2014-2023 period was used as the basis for calculating flood discharge using the Rational method and Nakayasu Synthetic Unit Hydrograph (HSS). The calculation results showed that the peak flood discharge for the 10, 25, and 50-year return periods reached 599.71 m³/det, 648.91 m³/det, and 682.82 m³/det using the Rational method, and 835.01 m³/det, 888.68 m³/det, and 922.90 m³/det using the Nakayasu HSS method, respectively. Flow simulations with HEC-RAS indicated that some river cross sections, especially at STA 27+950, 28+050, and 28+100, were unable to accommodate the maximum discharge, causing runoff outside the channel. This finding indicates that the capacity of the existing channel is not adequate to safely channelize flood flows. The results of this study are expected to serve as a technical reference in river normalization planning and more targeted and sustainable flood mitigation efforts.